2011
DOI: 10.1111/j.1532-5415.2011.03767.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Falls, Injury, and Disability

Abstract: Obesity appears to be associated with greater risk of falling in older adults, as well as a higher risk of greater ADL disability after a fall. Obesity (BMI ≥ 40 kg/m(2) ) may reduce the risk of injury from a fall. Further investigation of the mechanisms of obesity on falls and related health outcomes is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
166
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(187 citation statements)
references
References 31 publications
10
166
1
10
Order By: Relevance
“…A longitudinal study by Himes and Reynolds (2012) indicates that obese older adults are more likely to fall than others; moreover, obesity in Class 1 body mass index (BMI) 30.0-34.9 kg/m 2 , and Class 2 BMI 35.0-39.9 kg/m 2 was related to greater likelihood of more disability after a fall, whereas in obesity Class 3 BMI ≥ 40.0 kg/m 2 a protective effect was found, these people are significantly less likely to be injured in a fall than normal-weight individuals.…”
Section: Medell and Alexandermentioning
confidence: 99%
“…A longitudinal study by Himes and Reynolds (2012) indicates that obese older adults are more likely to fall than others; moreover, obesity in Class 1 body mass index (BMI) 30.0-34.9 kg/m 2 , and Class 2 BMI 35.0-39.9 kg/m 2 was related to greater likelihood of more disability after a fall, whereas in obesity Class 3 BMI ≥ 40.0 kg/m 2 a protective effect was found, these people are significantly less likely to be injured in a fall than normal-weight individuals.…”
Section: Medell and Alexandermentioning
confidence: 99%
“…Obesity is associated with an increased risk of falls and disability in older adults (1). Age-related decreases in skeletal muscle mass that occur concurrently with obesity, termed "sarcopenic obesity" may result in substantially increased risk of morbidity and functional decline (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data indicate an increased risk of falls related to obesity 5,6,18 . Mitchell et al 5 observed that the prevalence of falls among obese subjects was 30%, whereas among those with normal weight was only 23%.…”
Section: Discussionmentioning
confidence: 99%